Experiential Brand Deployment: Improving Tourism Brand Evaluations. (June 2017) - Chen, Hsiu-Li; Mathews, Shane
This article examines the use of an experiential branding process to help leisure resort businesses evaluate their brand. We integrate experiential marketing and the quality function development approach in combination to help understand the brand from the perspectives of both the consumer and firm, to help resort service businesses build their experience-oriented competitive brands. The value of this study is that it provides a real-world brand framework, especially those resorts with limited resources. Much is spoken about the influence of the brand and why it is important, but little is known about decisions related to developing a brand, especially for firms that have limited resources such as resort tourism operators. Tourism operators tend to be small-to-medium enterprises that do not necessarily have the capacity to do everything suggested. Therefore, we explore how firms assess the critical elements of their brand by using an integrated approach. For example, the study finds that, first, by using the quality function development method resorts can identify the most critical brand elements, and second, we identify the associated strengths of each brand element and confirm the identified resort's critical brand elements for investment. Results show the potential strategies to create a more holistic set of experiences.